Current status of the peach palm (Bactris gasipaes) germoplasm bank, Guapiles, Costa Rica. - Ríos-Reyes, Luis Diego (2016)
The objective of this study was to determine the current status of the peach palm germoplasm bank at Los Diamantes Experimental Station (BGPLD). Lost accessions were quantified and missing passport data for the remaining accessions was obtained. The passport data was obtained from the diary created by Jorge Mora Urpí, founder of the bank, in 1972. To complete the information of accessions without data, bibliographic resources were used. In 2013, a census was conducted to determine the number of surviving palm trees. Originally, the bank was composed of 7286 palms representing 837 accessions from nine countries. A total of 1471 individuals belonging to the western group and 1271 to the eastern group were identified. Currently, only 805 individuals survive (11.1%). A lower mortality was observed in the palms from the western group (62.2 ± 41.5%) compared to those in the eastern group (81.5 ± 19.6 %). The BGPLD is in a critical condition of deterioration. Urgent and concrete institutional policies are needed to rescue this important plant genetic resource.